135k views
2 votes
Determine the commutators of the operators a and a+,where a = (x + ip)/2 ^1/2 and a+ = (x - ip)/ 2 ^1/2

User Alfi
by
6.2k points

1 Answer

4 votes

Answer:

Given that:


a = ((x+ip)/(2))^{(1)/(2)} and
a+= ((x-ip)/(2))^{(1)/(2)}

if a , a+ commutator, it obeys
aa^+ = a^+a

First find:


aa^+ = ((x+ip)/(2))^{(1)/(2)} ((x-ip)/(2))^{(1)/(2)}

=
(((x)^2-(ip)^2)/(4))^{(1)/(2)}=(((x)^2+(p)^2)/(4))^{(1)/(2)}

Now;


a^+a =((x-ip)/(2))^{(1)/(2)} ((x+ip)/(2))^{(1)/(2)} = (((x)^2-(ip)^2)/(4))^{(1)/(2)}

=
(((x)^2-(ip)^2)/(4))^{(1)/(2)}=(((x)^2+(p)^2)/(4))^{(1)/(2)}

therefore,
aa^+ = a^+a which implies the operators a and a+ are commutators.


User PyMaster
by
5.5k points